Organization of future pilots’ self-study work in the process of learning English (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The paper deals with timeliness of self-study work as a part of educational process in general and future pilots’ training in particular. It states that continuing integration of science, education and manufacture requires training creative specialists whose educational activity gradually changes into professional one. The article points at the fact that self-study work forms students’ ability to solve tasks and develops skills to organize and realize own activity without outside management and assistance.The article emphasizes that students’ self-work is characterized by developing student’s knowledge and skills necessary for solving educational tasks as well as forming mental set on systematic knowledge acquisition and skills to get oriented in scientific information. It is also considered to be an important factor of student’s self-organization in mastering methods of professional activity and behavior. The effectiveness of students’ self-work depends on conditions of its organization, variety of tasks, students’ motivation, individual approach to its organization, feedback and a number of other factors.Three stages in the organization of aviation students’ self-study work in English are distinguished. Preparatory stage is aimed at working out recommendations and tasks for students. During the main stage students do the tasks, and the final stage is connected with checking, discussing the mistakes, correcting them.This paper also focuses on short analysis of different kinds of self-study work that can be used while studying English in an aviation educational institution. They are home reading, which is mainly focused on texts having professional character, taking part in student’s conferences, listening, writing essays, making projects. It is emphasized that usage of information technologies for self-study work is also an important element contributing to the effectiveness of future pilots’ training.
Keywords: self-study work; effectiveness; stages in the organization of aviation students’ self-study work; kinds of self-study work; management and control